Psychometric Properties of the Health Professionals Communication Skills Scale in University Students of Health Sciences - Juliá-Sanchis, Rocío (Int J Environ Res Public Health, 2020)
Communication is one of the determining factors of healthcare quality; however, a health model that prioritizes clinical over non-technical skills remains prevalent. The aims of this article were: (a) to validate a communication skills scale in a sample of fourth-year nursing degree students from two Spanish universities and (b) determine their perception of communication skills. The study included 289 fourth-year nursing undergraduate students with a mean age of 22.7 (SD = 4.87) years; 81.7% were female. The Health Professionals Communication Skills Scale (HP-CSS) questionnaire was adapted for use among nursing students. We analysed the psychometric properties and relationships with the variable attitudes toward communication skills. The HP-CSS showed a high internal consistency (0.88) and good fit of data to the model (TLI = 0.98; CFI = 0.97; RMSEA = 0.05 [95% CI = 0.04–0.06]). The total score and subscale scores correlated with the variable attitude towards communication skills. High scores were obtained for the students’ perception of communication skills. The HP-CSS is a valid and reliable tool to assess the communication skills in nursing students. This scale provides university teachers with a rapid and easily applied instrument to assess the level of communication skills and relationship with patients.